Performative Interiors: Terminological and Theoretical Reflections on the Term 'Performative' - Kassem, Ayman (UI Scholars Hub, 2019)
‘Performative’ is an emerging term in architectural discourse. The word ‘performative’ is able to describe spatial qualities and design approaches. The term is mostly linked to the concepts of open-form, and flexibility which are characters that give the spatial design a strategic aspect as the ability to anticipate and host predicted and unpredicted occurrences, and to adjust to future changes, which also gives architecture the character of an unfolding ‘event’ in time and in space. This paper seeks to investigate the terminological and the theoretical dimensions of the term ‘performative.’